Analysis of Production Cost on Income of Chocolate Farmers - Bustang Bustang; Selfiana Marintin Paembonan; Neks Triani; Masitah Masitah; Syahri Wahyuni (Agribusiness Journal, 2023)
This research aims to determine the production cost of cocoa producers in Ulunggolaka Village, Kolaka Regency in order to determine the income of chocolate producers in Ulunggolaka Village, Kolaka Regency. This research is quantitative research. The population studied in this study consisted of two groups of farmers from Ulunggolaka village, Kolaka district, comprising 45 clove producers. In the meantime, the sample was determined using the Slovin formula, with the final result being 31 clove producers. The data analysis used is sales formula, production cost formula and revenue formula. The results of this research suggest that the average income of farmers in a year is IDR. 10,986,209 per person and this income was generated from the total income of farmers amounting to Rp. 10,986,209. 13,311,000 for each respondent. The total production cost is IDR. 2,324,791 per person with a sale price of Rp. 29,000 per kilogram. The production cost consists of variable costs of IDR 2,154,194 per person, while fixed costs are IDR 170,597 per person.